Reduction of Power Losses Based on Generalized Two-level PWM Algorithm for a Nine-switch VSI - Neerakorn Jarutus (2018)
© 2018 IEEJ Industry Application Society. The generalized two-level pulse-width-modulation (PWM) algorithm for the nine-switch voltage source inverter (VSI) is proposed for more simplicity of the implementation and significantly reducing the power losses compared with the conventional nine-switch PWM algorithm. In addition, a new power loss analysis method is also proposed to investigate the power loss reduction of the nine-switch VSI with the proposed PWM by synthesizing the voltage and current distribution models in line with the switching states. This method is simple and high accurate using a characteristic curve-based technique, and also remarkably able to be available for both conduction and switching loss analysis in only one point of view. The corresponding simulation results can well confirm the validity of the proposed PWM algorithm and the proposed power loss analysis method.